2016
DOI: 10.1007/164_2016_52
|View full text |Cite
|
Sign up to set email alerts
|

Application of GPCR Structures for Modelling of Free Fatty Acid Receptors

Abstract: Five G protein-coupled receptors (GPCRs) have been identified to be activated by free fatty acids (FFA). Among them, FFA1 (GPR40) and FFA4 (GPR120) bind long-chain fatty acids, FFA2 (GPR43) and FFA3 (GPR41) bind short-chain fatty acids and GPR84 binds medium-chain fatty acids. Free fatty acid receptors have now emerged as potential targets for the treatment of diabetes, obesity and immune diseases. The recent progress in crystallography of GPCRs has now enabled the elucidation of the structure of FFA1 and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…These studies, however, did not identify a potential charge partner for the carboxylate of the fatty acid near the extracellular surface and, indeed, concluded that the carboxylate of C10 was pointing downwards, deep into the cleft of the seven transmembrane domain core of the receptor and interacting with an asparagine located at position 104 in the primary amino acid sequence 3 . As we have highlighted recently 9 GPR84 and the β 2 -adrenoceptor are only distantly related whilst, of the currently available atomic level GPCR structures, the orexin OX 1 receptor 34 has highest overall sequence identity (31%) with GPR84. We, therefore, generated and employed a new homology model of GPR84 based on the transmembrane domain architecture of the OX 1 receptor (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…These studies, however, did not identify a potential charge partner for the carboxylate of the fatty acid near the extracellular surface and, indeed, concluded that the carboxylate of C10 was pointing downwards, deep into the cleft of the seven transmembrane domain core of the receptor and interacting with an asparagine located at position 104 in the primary amino acid sequence 3 . As we have highlighted recently 9 GPR84 and the β 2 -adrenoceptor are only distantly related whilst, of the currently available atomic level GPCR structures, the orexin OX 1 receptor 34 has highest overall sequence identity (31%) with GPR84. We, therefore, generated and employed a new homology model of GPR84 based on the transmembrane domain architecture of the OX 1 receptor (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To try to identify how a MCFA might interact with GPR84 we turned to homology modelling studies. Although GPR84 is not closely related to the other GPCRs that respond to either short chain (FFA2, FFA3) or long chain (FFA1, FFA4) fatty acids 8 , 9 , in each of the other cases the carboxylate of the fatty acid is co-ordinated by one or more arginine residues located at or near the extracellular surface 12 14 . A previous effort to model the structure of GPR84 and to predict the mode and orientation of binding of C10 developed a receptor homology model based on the atomic level, active-state structure of the β 2 -adrenoceptor 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations